Accretion disks and relativistic line broadening in boson star spacetimes - Rosa, João Luís (2024)
In this work, we analyze the observational properties of static, spherically symmetric boson stars with fourth and sixth-order self-interactions, using the Julia-based general-relativistic radiative transfer code skylight. We assume the boson stars are surrounded by an optically thick, geometrically thin accretion disk. We use the Novikov-Thorne model to compute the energy flux, introducing a physically based accretion model around these boson star configurations. Additionally, we calculate the relativistic broadening of emission lines, incorporating a lamppost corona model where the relativistic effects arising from the boson star spacetime have been taken into consideration. Our results show distinct observational features between quartic-potential boson stars and Schwarzschild black holes, owing to the presence of stable circular orbits at all radii around the former. On the other hand, compact solitonic boson stars, which possess an innermost stable circular orbit, have observational features closely similar to black holes. This similarity emphasizes their potential as black-hole mimickers. However, the compact boson stars, lacking an event horizon, have complex light ring structures that produce potentially observable differences from black holes with future generations of experiments.